Wpływ zanieczyszczenia powietrza na układ oddechowy dzieci - przegląd dotychczasowych badań - Biela-Mazur, Jadwiga; Woźniak, Kamila; Doniec, Zbigniew (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The influence of air pollution on childrens' respiratory system has become a common, widespread health problem. It occurs to have influence not only on asthma exacebrations, but also on lung development and function. We conducted a systematic review on recent researches presenting influence of both short- and long-term air pollution exposure in children.